2019
DOI: 10.3390/ijms20225720
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Signature of Survival Prediction for Kidney Renal Cell Carcinoma by Multi-Omic Data Analysis

Abstract: Kidney renal cell carcinoma (KIRC), which is the most common subtype of kidney cancer, has a poor prognosis and a high mortality rate. In this study, a multi-omics analysis is performed to build a multi-gene prognosis signature for KIRC. A combination of a DNA methylation analysis and a gene expression data analysis revealed 863 methylated differentially expressed genes (MDEGs). Seven MDEGs (BID, CCNF, DLX4, FAM72D, PYCR1, RUNX1, and TRIP13) were further screened using LASSO Cox regression and integrated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 75 publications
4
47
0
Order By: Relevance
“…After testing for collinearity, stepwise multivariate Cox regression analysis was performed to establish the IRG-derived risk signature in primary LGG. The following formula based on a combination of Cox coefficient and gene expression was used to calculate the risk score (Lossos et al, 2004;Chen et al, 2007;Hu et al, 2019):…”
Section: Establishment Of the Immune-related Risk Signaturementioning
confidence: 99%
“…After testing for collinearity, stepwise multivariate Cox regression analysis was performed to establish the IRG-derived risk signature in primary LGG. The following formula based on a combination of Cox coefficient and gene expression was used to calculate the risk score (Lossos et al, 2004;Chen et al, 2007;Hu et al, 2019):…”
Section: Establishment Of the Immune-related Risk Signaturementioning
confidence: 99%
“…BID promotes the occurrence and metastasis of ccRCC by altering TNF signals [ 20 ]. Other studies have shown that BID is closely related to the survival prognosis of ccRCC [ 21 23 ]. SPHK1 can be used as a target gene of HIF-1 to influence the prognosis of ccRCC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silencing of TRIP13 can suppress cell growth and metastasis of hepatocellular carcinoma by activating TGF-β1/SMAd3 signaling (47). TRIP13 is 1 of the 7 hypomethylated genes in kidney renal cell carcinoma that have been suggested as a prognostic factor (48). downregulation of ZNF878 has been suggested to be correlated with a poor prognosis of patients with LUAd (49).…”
Section: Multivariate -----------------------------------------------mentioning
confidence: 99%